2016
DOI: 10.4049/jimmunol.1501032
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A Prevents IFN-γ/IFN-γ Receptor Interaction and Attenuates Classical Activation of Human Alveolar Macrophages

Abstract: Lung surfactant protein A (SP-A) plays an important function in modulating inflammation in the lung. However, the exact role of SP-A and the mechanism by which SP-A affects IFN-γ–induced activation of alveolar macrophages (aMϕs) remains unknown. To address these questions, we studied the effect of human SP-A on rat and human aMϕs stimulated with IFN-γ, LPS, and combinations thereof and measured the induction of proinflammatory mediators as well as SP-A’s ability to bind to IFN-γ or IFN-γR1. We found that SP-A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Surfactant protein A was isolated from BAL of patients with alveolar proteinosis using a sequential butanol and octylglucoside extraction (11, 3033). The purity of SP-A was checked by one-dimensional SDS-PAGE in 12 % acrylamide under reducing conditions and mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfactant protein A was isolated from BAL of patients with alveolar proteinosis using a sequential butanol and octylglucoside extraction (11, 3033). The purity of SP-A was checked by one-dimensional SDS-PAGE in 12 % acrylamide under reducing conditions and mass spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…The microbicidal activity of native and recombinant human SP-A against Escherichia coli J5 was evaluated by bacterial killing assays as described previously (30). Levels of mouse SP-A from BAL, pleural exudate, or lung tissue were detected by western-blot analysis as reported elsewhere (11, 3033). Native human C1q was obtained from Abcam (Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…e functions of activated macrophages are regulated by mediators produced by T cells. e classically activated macrophages (M1) are regulated by interferon (IFN)-c and LPS [24], while alternatively activated macrophages (M2) are produced in response to IL-4 or IL-13 [25]. M2 macrophages have been shown to play a role in relief of inflammation and thus have decreased capacity to produce cytokines.…”
Section: Macrophages In Periodontitismentioning
confidence: 99%
“…Many studies have shown that STAT1 is the key transcriptional mediator of macrophage responses to IFN-γ. [15][16][17] Thus, we mainly focused on the downstream molecules of the STAT1 signaling pathway after IFN-γ stimulation in the following experiments, such as CXCL9 and some proinflammatory cytokines. [17][18][19] We speculated that Grx1/ STAT1-SSG might affect the M1 polarization of macrophages.…”
Section: Grx1 Depressed Activity and Function Of Stat1 In Macrophage mentioning
confidence: 99%